Water use by the Kalahari Lion Panthera Leo Vernayi - F.C. Eloff (Koedoe, 1973)
The extent to which the Kalahari lion can survive without having to drink water was investigated in the Kalahari Gemsbok National Park. It was found that while they may drink regularly where water is available, they may become completely independent of water under extreme desert conditions. Sufficient moisture for their needs seems to be obtained from the blood and body fluids of their prey and the vegetable components of theirdiet. Loss of water through evaporation is reduced by the lion'sleisurely way of life.